A Revision of the Methodology Used for Oral Expositions - Hernández-Guerra, Conchi (JOURNAL OF ADVANCES IN LINGUISTICS, 2018)
Oral expositions in English for foreign students are probably the most difficult activity they can deliver. Lack of practice and fluency, English level and self-awareness in the task make them feel nervous and stacked in many occasions. But, on the other hand, this is a necessary skill in the development of any degree or for future situations they may face in working environments. Added to this, teachers at high schools do as much as they can taking into account the working conditions: high ratio and few hours. The oral practice is time-consuming and students still do not see the importance of the task and feel more embarrassed than at University. The aim of this paper is to do some research on the preparation and delivery of an oral exposition. The exercise finishes with a survey offered to the students of the first year in the degree of Modern Languages at the University of Las Palmas de Gran Canaria. We can conclude that only pages on the net were checked in the preparation of the task and hardly the library of the Faculty; in the analysis of the exposition itself, they agree that they could do much better if they had practiced more often. Some proposals are offered in the conclusions.